Simulation-based performance evaluation of a multi-UGV transportation system - Lu, Meng. (2013)
Task sequencing and scheduling plays an important role in manufacturing and logistic systems. How to perform computational efficient task routing and scheduling imposes one of the major technical challenges for a large complex system. A promising solution is to utilize distributed planning strategies to overcome the complexity issue while making an acceptable sacrifice on the performance. In this project he needs to apply an existing task routing and scheduling approach to a multi-UGV system and evaluate the performance of finishing a finite number of given jobs. He is expected to develop a simulation package and create a multi-UGV operational scenario upon which task routing and scheduling is performed. Data collection and analysis are required to derive an affirmative conclusion about the effectiveness of the utilized routing and scheduling approach.